Fostering a Listening Community Through Testimony: Learning with Orphans of the Genocide in Rwanda - Alexandre Dauge-Roth (The University of Alabama, 2022)
As a teacher of French and Francophone studies, I am eager to provide meaningful contexts of conversation in which students can improve their linguistic proficiency and develop their cultural literacy through immersion experiences. However, what shapes a meaningful context of dialogue? Is an academically generated conversation equally meaningful for students and community partners? These questions led me to reevaluate the relationship between my students, myself, and potential Francophone interlocutors in designing a course on the representations of the genocide against the Tutsis in Rwanda.